Effects of ease of doing business and components of good corporate governance on foreign direct investment: Evidence from the Western Balkans - Arifi, Jon; Arifi, Erëza (Edelweiss Applied Science and Technology, 2024)
The research aims to quantify the effect of easy doing business (EDB) on foreign direct investments, especially their resulting consequences. Meanwhile, the research combines supplementary components that are associated with sound corporate governance practices, consisting of control of corruption (CC), lending interest rate (LIR), regulatory quality (RQ), and governance effectiveness (GE). To achieve the stated aim, the research employs secondary data from 2015-2022 and employs regression analysis as the analytical approach. Following examining outcomes, it is observed that EDB and GE have a statistically significant positive effect, while the variables resulting in a significantly negative effect on FDI were LIR and RQ. Concerning CC, there have been surprising results since it has harmful effects that are nevertheless statistically insignificant. Research from the perspective of science’s contribution and creative thought relies on the application of a quantitative approach with a mixture of variables that directly affect FDI. The discoveries of the research definitely will challenge numerous stakeholders who operate within this field, such as scholars, and researchers, while nonetheless not omitting the implication of members who are additionally competent in the legislative part. The conclusions of this research will encourage an in-depth review of the implications for policymaking. Specifically, it requires upgrading certain regulations to make them more attractive for FDI.